Electroluminescence from nonpolar n-ZnO/p-AlGaN heterojunction light-emitting diode on r-sapphire. (14th February 2017) - Chen, Jingwen; Zhang, Jun; Dai, Jiangnan; Wu, Feng; Wang, Shuai; Chen, Cheng; Long, Hanling; Liang, Renli; Zhao, Chong; Chen, Changqing; Tang, Zhiwu; Cheng, Hailing; et al.
Abstract: Nonpolar a- plane n-ZnO/p-AlGaN heterojunction light-emitting diodes (LEDs) have been prepared on r -sapphire substrate using metal organic chemical vapor deposition and a pulsed laser deposition method. The dominant electroluminescence emission at 390 nm from the interband transition in n-ZnO layer under a forward bias was observed. Interestingly, electroluminescence with emission at 385 nm based on an avalanche mechanism was also achieved under reverse bias. The mechanisms of both the electroluminescence and I – V characteristics are discussed in detail by considering the avalanche effect. It is demonstrated that the crystalline quality of n-ZnO, not the p-AlGaN, is what affects the performance of the nonpolar ZnO based avalanche LED.